The effect of lead on dermal exposure of plasticizers in toys and associated risk assessment - Chaoli Yuan; Mantuo Huang; Jiajia wan; Zijia Hong; Jiwen Luo; Lixuan Zeng; Yu Bon Man; Bingyan Lan; Xiaomin Yan; Yuan Kang (Emerging Contaminants)
Numerous studies reported risk assessment of human exposure to plasticizers in toys through dermal pathways, however, dermal bioaccessibility and percutaneous penetration of plasticizers under effects of lead had been seldom studied. In the present study, dermal bioaccessibility of plasticizers including phthalate esters and alternative plasticizers in toys were examined in artificial sweat and SSSM (synthetic sweat and sebum mixture), and percutaneous penetration of plasticizers were investigated by skin cells under individual plasticizers exposure or combined exposure conditions (plasticizers + lead). The present results indicated that dermal bioaccessibility of plasticizers in SSSM were higher than that in artificial sweat. DEHP (Di-2-ethylhexyl Phthalate) showed highest bioaccessibility among all the plasticizers, DEHT (Di (2-ethylhexyl) terephthalate) showed highest bioaccessibility among all the alternative plasticizers. DEHP and DEHT were selected to perform the cell absorption assay. Skin cell absorption assay demonstrated that MEHP (Mono-(2-ethylhexyl) phthalate) was the major metabolite of DEHP and the absorption percentage of DEHP was higher than that of DEHT. Compared to individual exposure of plasticizers, the absorption percentage of DEHP and DEHT in skin cells under the combined exposure condition were increased by 12.40 %–14.63 % and 8.35 %–9.84 %, respectively. Risk assessment indicated that the plasticizers in toy would not result in unacceptable risk for children, but the health risk of plasticizers in toys to children under combined exposure condition would be 1.5–2 times higher than that under individual exposure condition.